Analysis of Brand Preference of Soft drinks in the Global Environment - Banumathy, S.; Hemameena, M. (Indian Journal of Marketing, 2006)
One of the most competitive markets in the world at present is the soft drink market in which crores of rupees on advertisement and other promotional activities are being spent. It is one of the many sectors, registering steady growth over a hundred years throughout the world. In India, the soft drink industry is flourishing well with a wide range of brands comprising both popular international and national and regional branded soft drinks. In the present investigation, the impact of globalisation on brand preference of soft drinks and the factors determining the brand preference are studied.